INVEST IN THE BUSINESS OF THE FUTURE: CLOUD COMPUTING - Abdullajonov Davronjon; Abdullajonova Gulmira (Zeta Repository, 2023)
Cloud computing is when companies rent their equipment over the Internet or immediately provide some kind of service. According to the calculations of the statistical analysis service, the market of cloud solutions will double in the next 4 years, and 3 times in 10 years.